Ovoid amphorae as the first Roman provincial repertoire in Hispania Ulterior (the Guadalquivir valley) - García Vargas, Enrique (2020)
During the first century BC, the Guadalquivir valley joins the group of those producing ovoid amphorae in the Western Mediterranean, as it becomes one of the main exporting areas of agricultural commodities. This development took shape in the Augustan period and later, due to correlation between the necessities demanded by the State and the ability of the southern Hispanic territories to supply them. However, this process takes its first steps even earlier; from the early moments of the first century BC, the Guadalquivir valley apparently began a mass-production of agricultural goods, as is reflected in the amphora repertoire of Ulterior being then produced as the first Romanised provincial amphorae of the region. This article presents the most important ovoid forms produced in the Guadalquivir valley, paying particular attention to their form and their epigraphical features, as well as investigating their distribution in internal and external markets. Some other questions are treated too: the documented production places; the evolution of these products into a standardised format that closely follows the path of the transformation of the Guadalquivir valley into a highly specialised agricultural territory, based on olive-oil manufacture, just as would be case for the economy of the region during early Imperial times.